Data from: Heterozygosity at neutral and immune loci is not associated with neonatal mortality due to microbial infection in Antarctic fur seals ... - Litzke, Vivienne; Ottensmann, Meinolf; Forcada, Jaume; Heitzmann, Louise; Hoffman, Joseph Ivan (Dryad, 2019)
Numerous studies have reported correlations between the heterozygosity of genetic markers and fitness. These heterozygosity fitness correlations (HFCs) play a central role in evolutionary and conservation biology, yet their mechanistic basis remains open to debate. For example, fitness associations have been widely reported at both neutral and functional loci, yet few studies have directly compared the two, making it difficult to gauge the relative contributions of genome-wide inbreeding and functional genetic variation to fitness. Here, we compared the effects of neutral and immune gene heterozygosity on death from bacterial infection in Antarctic fur seal (Arctocephalus gazella) pups. We specifically developed a panel of 13 microsatellites from expressed immune genes and genotyped these together with 48 neutral loci in 234 individuals, comprising 39 pups that were classified at necropsy as having most likely died of bacterial infection together with a five times larger matched sample of healthy surviving ... : Supplementary Table S12362 microsatellite loci identified from the Antarctic fur seal transcriptome assembly that consist of a minimum of five short tandem repeats with perfect di-, tri- and tetranucleotide motifs.Supplementary Table S296 microsatellite loci selected for testing, comprising twenty that appeared polymorphic in silico as described by Hoffman and Nichols (2011) plus a further 76 loci that carried at least six repeat units.Supplementary Table S3Summary of the eleven immune microsatellites developed as part of this study.Supplementary Table S4Summary of the 48 neutral loci and the two previously published immune loci (Hoffman and Nichols, 2011) genotyped in this study, including their polymorphism characteristics in 234 Antarctic fur seal individuals.Supplementary File S1R-Markdown CodeSupplementary File S1R-Markdown PDFImmuneMicrosats_supplementaryarc_gaz_transcriptome.fastaarc_gaz_transcriptome.fastaarc_gaz_transcriptome_annotationsimmune_microsats_rawp3_in_fur_sealpvaluesTable of p-values for ...